2014
DOI: 10.5966/sctm.2014-0156
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cell Motility as a Potential Mesenchymal Stem Cell Marker for Multipotency

Abstract: Mesenchymal stem cells (MSCs) are expected to have a fundamental role in future cell-based therapies because of their high proliferative ability, multilineage potential, and immunomodulatory properties. Autologous transplantations have the "elephant in the room" problem of wide donor variability, reflected by variability in MSC quality and characteristics, leading to uncertain outcomes in the use of these cells. We propose life imaging as a tool to characterize populations of human MSCs. Bone marrow MSCs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Robust assays of MSC batch potency for ARDS are lacking. However, one recent study observed that cell motility can predict the differentiation potential of MSCs, which may provide a bioassay for characterizing MSC efficacy for certain disease conditions 36 . Another study also recently outlined that MSCs from young mouse donors were more effective than those from aging donors in reducing pulmonary fibrosis 37 .…”
Section: Mesenchymal Stromal/stem Cells For Acute Respiratory Distresmentioning
confidence: 99%
“…Robust assays of MSC batch potency for ARDS are lacking. However, one recent study observed that cell motility can predict the differentiation potential of MSCs, which may provide a bioassay for characterizing MSC efficacy for certain disease conditions 36 . Another study also recently outlined that MSCs from young mouse donors were more effective than those from aging donors in reducing pulmonary fibrosis 37 .…”
Section: Mesenchymal Stromal/stem Cells For Acute Respiratory Distresmentioning
confidence: 99%
“…In the host immune response after Mg implantation, the secretory cytokines were the vital players in the regulation of inflammation. Because of the pro-and anti-inflammatory properties of MSC and PBMC/macrophages, 40,95 this correlation was evaluated via the cytokine production of the inflammatory panel (TNFα, IFNγ, IL1β, IL2, IL4, IL5, IL10, IL13, IL1RA, and G-CSF) in the current TW coculture. In the presence of Mg, HUCPV secreted a lower number of pro-inflammatory TNFα, IFNγ, IL1β, and IL2 on day 4, when the Mg contents in the supernatants reached 18 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Migration rates determined from mathematical modelling can also serve as a measure of potency. Proliferative colonies with higher migration rates tend to be more chondrogenic than slower proliferating colonies (Bertolo et al, ). Non‐invasive assessments of cell morphology based on observed differences in culture‐expanded MSC populations of different trilineage differentiation capabilities may be informative in inferring colony‐level heterogeneity (Seiler et al, ).…”
Section: Discussionmentioning
confidence: 99%